A água e o vinho: a recepção das teorias aristotélicas da linguagem na doutrina de São Tomás de Aquino sobre o Verbo - Fedeli, Maria Ivone Pereira de Miranda (2017)
This research aims to show how, throughout his long intellectual journey, starting from an initial question about the compatibility of the theological terminology on the Divine Verb based upon the Prologue to the Gospel of Saint John and consolidated by Saint Augustine’s De Trinitate, by one side, and the concepts of the human verb formulated by Aristotle in De Anima, Peri Hermeneias and other texts on human language, by the other, Saint Thomas Aquinas manages to harmonize both authors, in a way which does not forsake Aristotle’s theory, but which further details and clarifies it, in a process of reflection in which data from faith are guidelines and, in a sense, the ultimate goal of the processes of reason and philosophy